Efisiensi Penyeimbangan Beban pada Gardu Distribusi PY094 untuk Mengurangi Susut Energi PLN ULP Pringgabaya - Salma Ashila Firdaus; Eka Nuryanto Budisusila (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
This study aims to analyze the operational condition of the distribution transformer at substation PY094, PLN ULP Pringgabaya, with a primary focus on identifying and calculating the level of load imbalance on the consumer side. Data were collected through direct measurements of electrical parameters, including voltage and current in each phase, followed by a detailed analysis of energy losses. The measurement results indicated a significant load imbalance. In Feeder B, the average phase currents were recorded at 103.8 A for phase R, 130.2 A for phase S, and 90.4 A for phase T. Meanwhile, in Feeder D, the average phase currents were 47.4 A for phase R, 18 A for phase S, and 20.4 A for phase T. This imbalance caused notable power losses in the distribution system, with an estimated daily energy loss of 28.94 kWh, assuming the system operates 12 hours per day. To address this issue, load balancing simulations were carried out using ETAP software. The simulation involved redistributing load values across each phase in the two main feeders. Feeder B was simulated at 46.82% of the transformer’s full capacity, while Feeder D was simulated at 12.38% of the total 160 kVA capacity. The simulation results demonstrated that redistributing the load significantly reduced the current imbalance, thereby minimizing power losses and improving the operational efficiency of the distribution substation. Therefore, load balancing strategies are essential for enhancing energy efficiency and ensuring the reliability of electricity supply in distribution networks.